Reproductive prefomance of goats in traditional livestock systems in communal areas in Zimbabwe - Monicat, F.; Keravec, J.; Borne, P.M. (International Livestock Centre for Africa, 1994)
Individual and herd performances of goats were monitored in nine communal areas in Zimbabwe, which are representative of the various traditionally managed production systems. Between 1 September 1990 and 1 November 1991, 6950 goats from 254 farms were monitored twice monthly on an individual basis. Results showed that the reproductive performance varied markedly with the natural and socio-economic environment of the animals. Animals in recently established communal areas performed better than those from both the old communal areas and the heavily degraded natural environments. The animals' potential was achieved through the individual techniques of their owners.